HIV-related Stigma in Rural and Tribal Communities of Maharashtra, India (Journal of Health, Population and Nutrition, 2013)
Stigma is a recognized barrier to early detection of HIV and causes great suffering for those affected. This paper examines HIV-related stigma in rural and tribal communities of Maharashtra, an area of relatively high HIV prevalence in India. The study used a mix of qualitative and quantitative methods to compare adult women and adolescents in a rural area, women in a rural area, and women in a tribal area. The respondents included 494 married women and 186 adolescents in a rural community and 49 married women in six tribal villages. HIV-related stigma was prevalent in all communities and was the highest among tribal and older respondents. High-risk behaviour was reported in both areas, accompanied with denial of personal risk. Our findings suggest that HIV may be spreading silently in these communities. To our knowledge, this is the first community-based study to make an in-depth assessment of HIV-related stigma in rural and tribal areas of India. By situating our findings within the broader discourse on stigma in the national and state-level data, this study helps explain the nature and persistence of stigma and how to address it more effectively among subcultural groups in India. DOI: http://dx.doi.org/10.3329/jhpn.v30i4.13291 J HEALTH POPUL NUTR 2012 Dec;30(4):394-403